2017
DOI: 10.3390/ijms18081670
|View full text |Cite
|
Sign up to set email alerts
|

Variation within Variation: Comparison of 24-h Rhythm in Rodent Infarct Size between Ischemia Reperfusion and Permanent Ligation

Abstract: The detrimental effects of myocardial infarction in humans and rodents have a 24-h rhythm. In some human cohorts however, rhythmicity was absent, while the time of maximum damage differs between cohorts. We hypothesized that the type of damage influences the 24-h rhythm in infarct size. Myocardial infarction was induced in 12-week-old C57BL/six mice at four different time-points during the day using either permanent ligation (PL) or 30-min of ischemia followed by reperfusion (IR), with a control group wherein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Studies in rodents have shown that the time of day at which an ischemia is triggered can influence the severity of a myocardial infarction [ 16 , 17 , 18 ]. Indeed, the infarct size in hearts subjected to ischemia at the sleep-to-wake transition was significantly increased compared to hearts subjected to ischemia at the wake-to-sleep transition.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in rodents have shown that the time of day at which an ischemia is triggered can influence the severity of a myocardial infarction [ 16 , 17 , 18 ]. Indeed, the infarct size in hearts subjected to ischemia at the sleep-to-wake transition was significantly increased compared to hearts subjected to ischemia at the wake-to-sleep transition.…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial infarction (MI) leading to heart failure (HF) was induced in 8-week-old mice by LAD ligation, as described [39,41]. All surgeries were performed between ZT01-ZT04, as this is consistent with prior studies and findings that MI tolerance is time-of-day dependent [18,39,41,72]. Briefly, mice were anesthetized with isoflurane, intubated, and ventilated (Harvard Apparatus model 687) throughout the surgery.…”
Section: Left Anterior Descending (Lad) Coronary Artery Ligationmentioning
confidence: 96%
“…(caption on next page) P. Mistry, et al Journal of Molecular and Cellular Cardiology 149 (2020) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] also being developed to promote the transfer of a multi-species community to recipients [86,87].…”
Section: Tablementioning
confidence: 99%
“…Not only food intake but also numerous cardiac parameters have a peculiar daily rhythm: blood pressure and heart rate are characterized by daily fluctuations ( 71 73 ). Moreover, numerous epidemiological studies have revealed that various adverse cardiac events, i.e., myocardial ischemia, sudden cardiac death, and ventricular fibrillation, occur more frequently during the morning ( 74 76 ). At molecular levels, different components of the cardiovascular system express circadian genes from smooth muscle cells ( 77 , 78 ) to cardiomyocytes ( 79 , 80 ).…”
Section: The Circadian System: An Orchestra Of Signals Synchronizes F...mentioning
confidence: 99%